2015
DOI: 10.1504/ijecb.2015.067681
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of stress distribution in ankle joint: simultaneous application of experimental and finite element methods

Abstract: Abstract:The goal of this study was to determine stress distribution in ankle joint by correlating with the strain distribution and its trend around tibia adjacent to the joint. Using an in-house device, an ankle from a cadaver was kept stable and loaded in various positions: neutral, dorsiflexion, plantar flexion, inversion and eversion. A total of six strain gauges were mounted around the shaft of the tibia, near the tibiotalar joint. This arrangement allowed us to measure deformations in the shaft of tibia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The difficulties in estimating the ankle contact pressure experimentally can be partially overcome by the use of in-silico models which simulate the contact of cartilage layers within the joints. Finite Element Analysis (FEA) has been widely used for the investigation of the joint contact pressure on subject-specific geometries of different joints, and researchers have tested and validated its predictions at the hip 12,13 , at the knee 14 , and at the ankle 15 . Hyperelastic 16 or multiphasic 17 descriptions of the cartilage can be treated within the framework of FEA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties in estimating the ankle contact pressure experimentally can be partially overcome by the use of in-silico models which simulate the contact of cartilage layers within the joints. Finite Element Analysis (FEA) has been widely used for the investigation of the joint contact pressure on subject-specific geometries of different joints, and researchers have tested and validated its predictions at the hip 12,13 , at the knee 14 , and at the ankle 15 . Hyperelastic 16 or multiphasic 17 descriptions of the cartilage can be treated within the framework of FEA.…”
Section: Introductionmentioning
confidence: 99%
“…Finite Element Analysis (FEA) has been widely used for the investigation of the joint contact pressure on subject-specific geometries of different joints, and researchers have tested and validated its predictions at the hip, 12 , 13 at the knee, 14 and at the ankle. 15 Hyperelastic 16 or multiphasic 17 descriptions of the cartilage can be treated within the framework of FEA. Numerical convergence problems and long computational time are however a common obstacle and they can be exacerbated when dealing with nonlinear materials and complex geometries.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of the validated FE models complement the proposed experimental setup in the study of TAR or FTAR preference by providing stress distribution patterns on interfaces and even in internal regions of the simulated parts, for example, prosthesis, polyethylene compartment and bones. 19,29,35 Assuming that stress shielding and uneven wearing patterns are two major factors for prosthesis loosening and dislocation, 16,36 then a more uniform stress pattern (see Figures 6-9) will be highly desirable for increasing the longevity and reliability of the joint replacement procedures. 19,37 Thus, the disadvantage of small reduction in the neighboring joints' movement, due to the applied STJ fusion, can be well compromised with an increased longevity of the replaced joint.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, any additional intervention that gives rise to more monotonic stress patterns in the prosthesis and its neighboring bones can likely increase its longevity. It was found that there is a more uniform stress distribution in fused STJ, compared with the normal one 19 . Moreover, the asymmetric stress distribution in the tibial component of the prosthesis is reported in the literature with higher stresses in the lateral side 20,21 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation